Pengaruh Fasilitas Pelayanan di Ruang Tunggu Domestik terhadap Kepuasan Penumpang di Bandar Udara Husein Sastranegara Bandung - Muhammad Fajar S Somadil Amin; Teguh Ariebowo (Universitas Maritim AMNI Semarang, 2024)
Based on the results of the researcher's observations at Husein Sastranegara Airport, Bandung, a problem was found in the form of complaints from passengers in the waiting room area which arose due to several facilities that were not functioning optimally, namely related to the increasing room temperature and the lack of seating areas in the passenger waiting room area so that not all passengers could get a seat. The lack of several of these facilities caused an uncomfortable feeling for the passengers who were in the waiting room area while waiting for their flight departure schedule. This study aims to determine whether there is an influence of domestic waiting room service facilities on passenger satisfaction at Husein Sastranegara Airport, Bandung and how big the influence is. This study uses a quantitative method with a research location at PT. Angkasa Pura II Husein Sastranegara International Airport Bandung, precisely in the domestic waiting room area at Husein Sastranegara International Airport Bandung. Surveys and observations are data collection techniques in this study. Based on the results of the study, it can be concluded that the results of the correlation table analysis of 0.764 using the interpretation of the r value are> 0.5 - 0.583 = strong correlation, it can be interpreted that the hypothesis H0 is rejected and H1 is accepted so that it shows the results that passenger satisfaction is influenced by service facilities, while the results of hypothesis testing in the study provide results that the magnitude of the influence of variable X (service facilities) on variable Y (passenger satisfaction) shows strong results by obtaining a correlation coefficient of 0.764 with a determination coefficient of 58.3%. with the remaining 41.7% influenced by other factors not studied by researchers such as eligibility, availability, cleanliness and other elements.